Spontaneous expression of magnetic compass orientation in an epigeic rodent: the bank vole, Clethrionomys glareolus - Oliveriusová, Ludmila; Němec, Pavel; Pavelková, Zuzana; Sedláček, František (Die Naturwissenschaften, 2014)
Magnetoreception has been convincingly demonstrated in only a few mammalian species. Among rodents, magnetic compass orientation has been documented in four species of subterranean mole rats and two epigeic (i.e. active above ground) species-the Siberian hamster and the C57BL/6J mouse. The mole rats use the magnetic field azimuth to determine compass heading; their directional preference is spontaneous and unimodal, and their magnetic compass is magnetite-mediated. By contrast, the primary component of orientation response is learned in the hamster and the mouse, but both species also exhibit a weak spontaneous bimodal preference in the natural magnetic field. To determine whether the magnetic compass of wild epigeic rodents features the same functional properties as that of laboratory rodents, we investigated magnetic compass orientation in the bank vole Clethrionomys glareolus (Cricetidae, Rodentia). The voles exhibited a robust spontaneous bimodal directional preference, i.e. built nests and slept preferentially along the north-south axis, and deflected their directional preference according to a shift in the direction of magnetic north, clearly indicating that they were deriving directional information from the magnetic field. Thus, bimodal, axially symmetrical directional choice seems to be a common feature shared by epigeic rodents. However, spontaneous directional preference in the bank vole appeared to be more pronounced than that reported in the hamster and the mouse. These findings suggest that bank voles are well suited for future studies investigating the adaptive significance and mechanisms of magnetic orientation in epigeic rodents.
Keywords: hnízdění; Magnetic Phenomena; Male; Female; magnetické jevy; ženské pohlaví; Arvicolinae; orientace; Nesting Behavior; mužské pohlaví; Animals; Orientation; zvířata